Effectiveness of Self for Online Entrepreneurship and Its Relationship with Academic Self-Esteem Among King Faisal University Students - Saleh, Dr. Shoeb (South Eastern European Journal of Public Health, 2024)
The rapid digital transformation globally has positioned online entrepreneurship as a vital modern economic domain. Self-efficacy plays a pivotal role in the success of individuals in this field, influencing their decision-making, innovation, and ability to overcome challenges. Similarly, academic self-esteem serves as a critical measure of students' confidence in their academic abilities, directly enhancing their performance in various activities. Against this backdrop, the present research aimed to examine: the level of self-efficacy in online entrepreneurship, the level of academic self-esteem, and the relationship between these two variables among students at King Faisal University. Adopting a descriptive approach, the study utilized the Self-Efficacy Scale for Online Entrepreneurship and the Academic Self-Esteem Scale. The sample consisted of 78 randomly selected students. Key findings revealed that the students exhibited an average level of self-efficacy in online entrepreneurship and a high level of academic self-esteem. Furthermore, a statistically significant correlation was identified between self-efficacy in online entrepreneurship and academic self-esteem. The study recommended enhancing students' knowledge of entrepreneurship through targeted training and showcasing successful entrepreneurial models to positively influence their perception of online entrepreneurship.